Effects of Second and Third Generation Oral Contraceptives and their Respective Progestagens on the Coagulation System in the Absence or Presence of the Factor V Leiden Mutation - Kemmeren, J. M.; Algra, A.; Meijers, J. C. M.; Bouma, B. N.; Grobbee, D. E. (Thrombosis and Haemostasis, 2002)
Compared to second generation, the use of third generation oral contraceptives has been associated with an increased risk of venous thrombosis especially in women with the factor V Leiden mutation. To find an explanation for these risk differences we investigated the effects of desogestrel- and levonorgestrel-containing oral contraceptives as well as their progestagens separately on the coagulation system in the absence or presence of the factor V Leiden mutation.In a single center, double blind trial, 51 women without and 35 women with the factor V Leiden mutation were randomized to either a second generation (30 µg ethinylestradiol/150 µg levonorgestrel) or a third generation (30 µg ethinylestradiol/150 µg desogestrel) oral contraceptive. After two cycles of use and a wash-out period of 2 menstrual cycles, the participants received the corresponding progestagen-only preparation containing 150 µg levonorgestrel or 150 µg desogestrel. In plasmas of the participating women fragment 1+2, factor V, VII, VIII, IX, X and XI were determined.Both combined oral contraceptives induced a decrease in factor V, whereas the levels of all other coagulant parameters increased. However, in women without the factor V Leiden mutation the effects of desogestrel-containing preparations were significantly different compared to levonorgestrel-containing oral contraceptives for factor V (−8.0; 95% Cl −13.4 to −2.6), factor VIl (26.8; 95% Cl 15.5 to 38.0) and factor IX (−9.6; 95% Cl −16.2 to −3.2). When these women used progestagen-only pills, a differential effect between desogestrel and levonorgestrel was only found for factor IX (−6.5; 95% CI –11.4 to –1.5).In carriers of the factor V Leiden mutation desogestrel-containing oral contraceptives induced more pronounced changes in factor V (−14.2; 95% CI −22.4 to −6.0) and factor VII (36.1; 95% CI 19.7 to 52.6) compared to levonorgestrel-containing oral contraceptives. Comparing desogestrel- and levonorgestrel-only, only for factor V a differential effect was found in these women (−9.5;95% CI –18.3 to –0.6).It appears that desogestrel-containing oral contraceptives have a more pronounced effect on the coagulation system than levonorgestrelcontaining oral contraceptives which may be explained by a less effective compensation of the thrombotic effect of ethinylestradiol by desogestrel.
Keywords: Oral contraceptives; levonorgestrel; desogestrel; coagulation; factor V Leiden